PEMBAGIAN WARISAN MENURUT HUKUM ADAT DAYAK KANTUK TERHADAP AHLI WARIS YANG KELUAR RUMAH BILIK DI DESA NANGA KENEPAI KABUPATEN KAPUAS HULU - NIM. A1012211069, CRESSENSIA TASYA NANA ELLA (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractThis study discusses the distribution of inheritance to the heirs who came out of the booth house in Nanga Kenepai Village, Kapuas Hulu Regency. The problem in this study is whether the heirs who leave booths get their customary parts in the law of sacks. This study aims to obtain data and information as well as a picture of the implementation of the distribution of inheritance, revealing the heir